If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-1=-4(9-x)+3-2(x-7)
We move all terms to the left:
-1-(-4(9-x)+3-2(x-7))=0
We add all the numbers together, and all the variables
-(-4(-1x+9)+3-2(x-7))-1=0
We calculate terms in parentheses: -(-4(-1x+9)+3-2(x-7)), so:We get rid of parentheses
-4(-1x+9)+3-2(x-7)
determiningTheFunctionDomain -4(-1x+9)-2(x-7)+3
We multiply parentheses
4x-2x-36+14+3
We add all the numbers together, and all the variables
2x-19
Back to the equation:
-(2x-19)
-2x+19-1=0
We add all the numbers together, and all the variables
-2x+18=0
We move all terms containing x to the left, all other terms to the right
-2x=-18
x=-18/-2
x=+9
| -2=x-7x-2 | | 2x-3x+7=12 | | x/2.3=-4.5 | | 4=(7c+3)+ | | 1/x=9 | | -x-14+9x-14=44 | | 2(4w+9)/4=-9 | | 1+6m=1+7m | | (2x-28)=90 | | 2x+1=-11+5x | | 4.5+(4.5*19)=x | | 8(x-1)=6x+13 | | 12-3(y-5)=21 | | 3(11x+10)=33x-1 | | 16-7m=1-4m | | 32x=2.5x-10.5 | | -8(1+2x)-32=-8 | | 5-t/4=14 | | 5c-26=-4 | | x.x=7x | | 52+2w=56 | | m=-2(-3,-5) | | 20p+12+7p+9=21 | | 6x-44=6x-44 | | y+19y=90 | | -8(x+6)+2(6x+8)=-28 | | X=96-16m | | X-6=-2+5x | | 40+10x=300 | | 82.0^2=12.5xA | | (8x+5)=(5x-19) | | 2000=25x+50 |